(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) is very necessary in diagnosis and treatment of some biliopancreatic disorders on pediatrics. There are few published data on this issue even in major centers around the world. Aims: Initial review of results and complication of ERCP in children. Materials and Methods: Descriptive study enrolled 10 retrospective and 5 prospective patients who performed ERCP in Vietnam National Children’s Hospital from July 1, 2018 to November 12, 2021. Results: 8/15 (53,3%) boys and 7/15 (46,7%) girls from 6 to 15 years old. The indications of ERCP included recurrent pancreatitis in 11/15 (73,3%) children, choledocholithiasis 3/15 (20%), biliary fistula post-liver transplantation 1/15 (6,7%). The cannulation success rate in the overall procedure was in 13/15 patients (86,7%). Diagnose after ERCP were pancreatic duct dilatation by stones in 5/15 (33,3%) children, choledocholithiasis 2/15 (13,3%), pancreatic duct dilatation without reason 2/15 (13,3%), choledochal dilatation without reason 1/15 (6,7%), choledochal fistula 1/15 (6,7%), normal results 2/15 (13,3%) and failure 2/15 (13,3%). Interventional success rate was 100% (pancreatic stent in 7/7 children, stone extraction 7/7 and sphincterotomy 2/2. Acute pancreatitis after ERCP was 5/15 patients (33,3%). Conclusion: ERCP in children had high diagnostic value (86.7%), effective in pancreaticobiliary disease treating (100%) and safe.